KARAKTERISTIK REMAJA HAMIL UMUR 10-21 TAHUN DI INDONESIA (CHARACTERISTICS OF PREGNANT ADOLESCENTS AGED 10-21 YEARS IN INDONESIA) - Anies Irawati; Sri Prihatini (Persagi, 2010)
ABSTRACT Introduction: Adolescence is a time of rapid growth (growth spurt). Pregnancy is a vulnerable condition, meaning that the health status of mothers during pregnancy determines the outcome of pregnancy. At this age young people still need the nutrients to grow but must bear the burden of pregnancy. Objectives: to know the characteristics of adolescent Indonesian pregnant women. Methods: The data presented are the result of analysis of secondary data Basic Health Research (Riskesdas) 2010. The data were analyzed descriptively using SPSS version 17.0. Results: Most of subject come from marginal socio-economics status (below elementary school, unskill labour, living in rural area, low income expenditure). Also, most of subject consumed macro-micro nutrient below Indonesian Recommended Dietary Allowance (RDA). Forty percent young (19-21 years) pregnant women pregnancy at risk. Conclusion: Most adolescent pregnant women live in an environment unfavorable to the growth of the fetus. Recommendation: Adolescent pregnancy should be prevented through improved socio-economic status, and most importantly the increase is in education and counseling adolescent the risk of adolescent pregnancy. [Penel Gizi Makan 2010, 33(2): 110-116] Keywords: pregnancy, adolescent, nutrition